Features of the modelled stress-strain state dynamics prior to the M7.1 2019 Ridgecrest earthquake in Southern California - Bondur V.; Gokhberg M.; Garagash I.; Alekseev Dmitry Aleksandrovich (Russian Journal of Earth Sciences)
The paper is concerned with the analysis of the simulated stress-strain state (SS) parameters of the earth's crust over the four-year period preceding the M7.1 2019 Ridgecrest earthquake in Southern California. SS parameters have been calculated using a detailed geomechanical model, taking into account an ongoing weak seismicity catalog data. Cyclic patterns are identified in the observed shear strain anomalies, with estimation of their spatial and temporal characteristics, and an attempt is made to track the influence of the local displacement direction and periodic migration of shear strain anomalies in the upper crust on the earthquake preparation. Finally, we discuss the role of the observed regularities in terms of existing models describing the earthquake preparation process.